2020
DOI: 10.3389/fmicb.2020.02017
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Is a Better Competitor Than Other Lactic Acid Bacteria in the Initial Colonization of Colon of Healthy Newborn Babies at First Week of Their Life

Abstract: Initial colonization of human gut by bacteria is an important step in controlling its microbiota and health status. This study followed the initial colonization by lactic acid bacteria (LAB) in colon of new born babies through following its occurrence in their stool at first week of their life. The LAB occurrence in the neonates’ stool was followed on MRS agar medium. The isolated LAB from male and female newborn babies of normal birth and cesarean section surgical delivery were molecular biologically identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
1
15
0
1
Order By: Relevance
“…No E. coli or other enteric bacteria were detected in first-pass meconium on eosin-methylene blue (EMB) agar, LB agar, or MacConkey agar. The first-pass meconium also showed no viable lactic acid bacteria (LAB) on de Man Rososa Sharpe (MRS) agar medium in this study or in a previous study ( 29 ) where LAB were detected in second-day stool and later. Despite several reports presenting a microbiome in placenta, amniotic fluid, and meconium, the viability and function of these microbiomes is not fully clear yet.…”
Section: Discussionsupporting
confidence: 70%
“…No E. coli or other enteric bacteria were detected in first-pass meconium on eosin-methylene blue (EMB) agar, LB agar, or MacConkey agar. The first-pass meconium also showed no viable lactic acid bacteria (LAB) on de Man Rososa Sharpe (MRS) agar medium in this study or in a previous study ( 29 ) where LAB were detected in second-day stool and later. Despite several reports presenting a microbiome in placenta, amniotic fluid, and meconium, the viability and function of these microbiomes is not fully clear yet.…”
Section: Discussionsupporting
confidence: 70%
“…Pregnant women, newborns, and the elderly are typically at greater risk of infection due to undeveloped or weakened immune systems. Research has demonstrated that supplementation with probiotics in the elderly leads to the growth of potentially beneficial intestinal bacteria but also leads to the increased activation of a non-specific immune response [ 71 ]. In some Western European countries, a fermented milk drink called “Gaio” (yogurt) is available, containing bacteria called “Causido,” which includes the E. faecium K-77D strain and two strains of Streptococcus termophilus .…”
Section: Enterococci As Probioticsmentioning
confidence: 99%
“…Thus, E. coli might in addition to other facultative anaerobes act as initial servant bacterium which consumes molecular oxygen gas for installing anaerobiosis for colon colonization by microaerobic and anaerobic bacteria such as Lactobacilli. The Lactobacilli are of the initial colonizing bacteria of colon in healthy newborn babies [8]. Lactobacillus sp is usually found in babies colon where it plays important healthy roles [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…This ability of E. coli to utilize lactose might help for its early colonization of the neonates' colon. Thus, along with early colonization of the neonates' colon by lactic acid bacteria (LAB) [8], E. coli also has suitable nutritional conditions explaining their good ability for initial colonization of the neonates' colon where milk retaining lactose is the only diet provided to the neonates through either breast or formula feeding. This also support our conclusion that initial colonization of E. coli is postnatal where milk feeding of the newborn babies confers a viable nutritional requirement of this bacterium and many other health bene cial lactose fermenting taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation